2005
DOI: 10.2166/wst.2005.0363
|View full text |Cite
|
Sign up to set email alerts
|

Effluent quality from 200 on-site sewage systems: design values for guidelines

Abstract: The quality of effluent from an on-site sewage treatment system is a critical factor in designing the disposal area and, hence, ensuring the sustained performance of the system. Contaminant concentrations in effluent are typically specified in regulatory guidelines or standards; however, the accuracy of these guideline values are brought into question due to the poor performance of septic tanks and the high failure rates of disposal systems reported here and elsewhere. Results from studies of septic tank efflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 2 publications
1
8
0
1
Order By: Relevance
“…Surveys indicate that at least 20 % of these systems are malfunctioning; over half of all US septic systems are over 30-yr old (US EPA, 2005). Old and improperly maintained systems are prone to failure and provide inadequate conditions for the effluent treatment processes including physical filtration, surface adsorption, sedimentation, and inactivation of the contaminants in the soil (Canter, 1997;Charles et al, 2005). Leachate from septic systems has been identified as a major potential source of groundwater contamination with nitrate, pharmaceutically active compounds (PhACs), endocrine active substances (EAS), other household chemicals, as well as pathogens such as bacteria, viruses, helminths, and protozoa (Perkins, 1984;US EPA, 1998, 2002aGerba and James, 2005;Carroll et al, 2006;Fong et al, 2007;Stanford et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys indicate that at least 20 % of these systems are malfunctioning; over half of all US septic systems are over 30-yr old (US EPA, 2005). Old and improperly maintained systems are prone to failure and provide inadequate conditions for the effluent treatment processes including physical filtration, surface adsorption, sedimentation, and inactivation of the contaminants in the soil (Canter, 1997;Charles et al, 2005). Leachate from septic systems has been identified as a major potential source of groundwater contamination with nitrate, pharmaceutically active compounds (PhACs), endocrine active substances (EAS), other household chemicals, as well as pathogens such as bacteria, viruses, helminths, and protozoa (Perkins, 1984;US EPA, 1998, 2002aGerba and James, 2005;Carroll et al, 2006;Fong et al, 2007;Stanford et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 200 septic tanks in Australia, Charles et al [36] found that septic wastewaters were much stronger than expected, leading to poor plant performance. They proposed that the 80th percentile concentration of septic tank effluent be adopted as the design value for sizing secondary treatment units to prevent overloading.…”
Section: Parameter Phmentioning
confidence: 99%
“…Numerous studies have been carried out concerning SFVDF systems in the field of ODWT in order to determine their behaviour and the characteristics of the materials to be used in order to obtain good sewage treatment performance (Bruen and Piluk, 1994;Chabaud et al, 2006a;Charles et al, 2005;Jayarathne et al, 2007;Jenssen and Siegrist, 1990;Rolland, 2009;Wanko et al, 2005;Whitehead and Geary, 2000).…”
Section: Context and Objectivesmentioning
confidence: 99%